Optimalisasi Pengelolaan Keuangan UMKM: Faktor Sistem Informasi Akuntansi, Literasi Keuangan, dan Persepsi Risiko - Saidi, Julita; Luthfi Iznillah, Muhammad; Natariasari, Riska (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2024)
This study investigates the impact of financial literacy and risk perception on MSMEs' financial management behavior, focusing on the mediating role of Accounting Information System (AIS) characteristics. The research was conducted on business actors in the Car and Motorcycle Repair and Maintenance sector and the Accommodation and Food and Beverage Services sector in Pekanbaru City, Indonesia, with a population of 2,046. A sample of 323 was determined using the Krejcie and Morgan formula with a Proportionate Stratified Random Sampling technique. Primary data were collected through questionnaires and analyzed using SEM-PLS with WarpPLS version 8.0. The results indicate that financial literacy and risk perception have a significant positive impact on financial management behavior, with AIS characteristics effectively mediating these relationships. These findings highlight the importance of improving financial literacy, enhancing risk perception, and optimizing AIS implementation to support sustainable financial management for MSMEs.